Development of an enzyme-linked immunosorbent assay (ELISA) for determining neutrophil elastase (NE) – a potential useful marker of multi-organ damage observed in COVID-19 and post-Covid-19 (PCS) - Adamiec-Mroczek, Joanna; Kluz, Joanna; Chwałek, Sandra; Rabczyński, Maciej; Gostomska-Pampuch, Kinga; Lewandowski, Łukasz; Misiuk-Hojło, Marta; Ponikowska, Beata; Chourasia, Goutam; Dumas, Ilias; Gamian, Andrzej; Fiodorenko-Dumas, Żanna; et al. (Frontiers in Molecular Biosciences, 2025)
BackgroundThe ongoing post-COVID-19 syndrome (PCS) epidemic, causing complications of diverse etiology, necessitates the search for new diagnostic markers and the development of widely accessible methods for their detection. This would enable the prognosis of PCS progression and faster implementation of targeted treatments. One potential marker is neutrophil elastase (NE), whose elevated levels in the blood during PCS may result from organ damage caused by increased secretion of severe inflammatory mediators or amyloidosis resulting from the interaction of NE with SARS-CoV-2. The aim of this publication is to present a step-by-step method for designing an enzymatic ELISA test, enabling the quantitative assessment of NE in the blood serum of patients.MethodsNE was measured using the designed ELISA test.ResultsThe study outlines all the steps necessary for designing and optimizing the ELISA test, including the selection of standards, primary and secondary antibodies, and their dilutions. Using the test, elevated NE levels were demonstrated in patients with advanced-stage diabetic nephropathy after symptomatic COVID-19, compared to a relative group of patients sampled before COVID-19.ConclusionThe undertaken efforts enabled the development of a test with high performance parameters (initially set sensitivity: ≥40 pg/μL; intra-assay precision: 7%; inter-assay precision <20%). No significant cross-reactivity with other tested proteins was observed. Serial dilution of plasma samples resulted in a proportional decrease in signal intensity.